A 500 pc volume-limited sample of hot subluminous stars: I. Space density, scale height, and population properties - Dawson, Harry; Geier, S.; Heber, U.; Pelisoli, I.; Dorsch, M.; Schaffenroth, V.; Reindl, Nicole; Culpan, R.; Pritzkuleit, M.; Vos, J.; Soemitro, A. A.; Roth, M. M.; et al. (Astronomy and astrophysics, 2024)
We present the first volume-limited sample of spectroscopically confirmed hot subluminous stars out to 500 pc, defined using the accurate parallax measurements from the Gaia space mission data release 3 (DR3). The sample comprises a total of 397 members, with 305 (∼77%) identified as hot subdwarf stars, including 83 newly discovered systems. Of these, we observe that 178 (∼58%) are hydrogen-rich sdBs, 65 are sdOBs (∼21%), 32 are sdOs (∼11%), and 30 are He-sdO/Bs (∼10%). Among them, 48 (∼16%) exhibit an infrared excess in their spectral energy distribution fits, suggesting a composite binary system. The hot subdwarf population is estimated to be 90% complete, assuming that most missing systems are these composite binaries located within the main sequence (MS) in the Gaia colour-magnitude diagram. The remaining sources in the sample include cataclysmic variables, blue horizontal branch stars, hot white dwarfs, and MS stars. We derived the mid-plane density ρ0 and scale height hz for the non-composite hot subdwarf star population using a hyperbolic sechant profile (sech2). The best-fit values are ρ0 = 5.17 ± 0.33 × 10−7 stars pc−3 and hz = 281 ± 62 pc. When accounting for the composite-colour hot subdwarfs and their estimated completeness, the mid-plane density increases to ρ0 = 6.15+1.16 −0.53 × 10−7 stars pc−3. This corrected space density is an order of magnitude lower than predicted by population synthesis studies, supporting previous observational estimates.